Review on solvent extraction methods of Lignin from Oil Palm Empty Fruit Bunches (OPEFB) - Pairon, Mohammad Shahrizad; Ali, Fathilah; Ahmad, Farah; Anuar, Hazleen; Abdul Rahman, Nurul Amirah; Mirghani, Mohamed Elwathig Saeed; Suhr, Jonghwan; Thomas, Sabu (Taylor & Francis Online, 2022)
A large amount of crude palm oil production in South East Asia (SEA) is causing the production of a vast amount of agricultural waste from the palm oil industry. Oil palm empty fruit bunch (OPEFB) is one of the agricultural wastes with high lignocellulose content. Lignin is the lignocellulose component that has the potential to be used as fuel for energy production and as a filler in composite materials. This review provides information on the solvent extraction methods used such as alkaline treatment, organosolv treatment, and deep eutectic solvent treatment to extract the lignin from lignocellulose OPEFB. The extracted lignin from different solvent extraction methods also gave different properties of lignin. In conjunction with that, catalyst and enzyme have been used to overcome the limitations of solvent extraction methods.